Determination of feasibility analysis of wind turbines using weibull parameter for chad / Marcel Hamda Souloukngaa & Hasan Huseyin Coban - Souloukngaa, Marcel Hamda; Coban2, Hasan Huseyin (Universiti Teknologi MARA Cawangan Sarawak, 2022)
Wind energy is one of the most important renewable energy sources whose technology and use have shown the fastest development and the economy has become competitive with fossil-based energy sources. To assess the potential of wind energy as a source of electricity generation, this paper uses the Weibull probability density function for three sites. Five wind turbines are considered for the study. The standard method is used to determine the values of the Weibull parameters. The average wind speed was measured and collected at the General Directorate of National Meteorology at 10 m altitudes. The results obtained show that the turbine capacity factor for three sites ranges from 0.03% to 6.47% (Enercon-70); 0.09% to 13.50% (Enercon-82); 0.04% to 9.27% (Nordex N90); 0.03% to 9.87% (Nordex S77) and 0.07% to 11.63% (Vestas V90-20).